2006
DOI: 10.2174/156652406778018671
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Neovascularization and Imaging

Abstract: Neovascularization in atherosclerotic plaques is particularly prominent in complicated lesions, and has been recently identified as a marker of plaque vulnerability. This observation has led to a growing interest in the development of imaging techniques with the ability to visualize and quantify the extent of plaque neovascularization. Such feature may play an important role in identifying those lesions more prone to destabilization and rupture, and in the guidance and monitoring of therapeutic interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 101 publications
(108 reference statements)
1
9
0
Order By: Relevance
“…11 For these reasons, plaque remodeling has been the target of medical therapies, such as statins, aiming at the possibility of transforming an unstable plaque into a more stable plaque, reducing the cerebrovascular risk. 12 In our patients, studied with ultrasound contrast pulse sequencing and SonoVue, we observed that UCA penetrates easily in the fibrous and fatty tissue and, according to our histological findings and to recent observations, 4,13 it is related to the plaque vascularization. The constant observation of a little vessel under ulcerations may further support the hypothesis that intraplaque hemorrhage may be related to the rupture of newly formed intraplaque microvessels, a triggering factor for further embolic processes.…”
Section: Discussionsupporting
confidence: 78%
“…11 For these reasons, plaque remodeling has been the target of medical therapies, such as statins, aiming at the possibility of transforming an unstable plaque into a more stable plaque, reducing the cerebrovascular risk. 12 In our patients, studied with ultrasound contrast pulse sequencing and SonoVue, we observed that UCA penetrates easily in the fibrous and fatty tissue and, according to our histological findings and to recent observations, 4,13 it is related to the plaque vascularization. The constant observation of a little vessel under ulcerations may further support the hypothesis that intraplaque hemorrhage may be related to the rupture of newly formed intraplaque microvessels, a triggering factor for further embolic processes.…”
Section: Discussionsupporting
confidence: 78%
“…As a matter of fact, an enhanced assessment of the arterial lumen and plaque morphology and an improved resolution of carotid intima-media thickness can be obtained [21, 22]. Consistent data also report that the direct visualization of adventitial vasa vasorum and plaque neovascularization is now possible with this simple, low cost, minimally invasive and in vivo technique[22,23,24,25,26]. …”
Section: General Considerationsmentioning
confidence: 95%
“…Carotid ultrasound, with ultrasound contrast agents (UCAs), is an emerging valuable tool to obtain more accurate data on carotid atherosclerosis, providing an enhanced assessment of the arterial lumen and plaque morphology and an improved resolution of carotid intima-media thickness [21]. Furthermore, recent observations have demonstrated that contrast carotid ultrasound may also identify adventitial vasa vasorum and plaque neovascularization [22,23,24,25,26], with the principal advantage of being a simple, low cost and minimally invasive technique available in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process, called neoangiogenesis, is primarily triggered by local hypoxic states [65]. Progredient neoangiogenesis has a direct connection to increased plaque instability.…”
Section: Molecular Probes and Contrast Agents For Displaying Angioneomentioning
confidence: 99%